Wide-open desert : a queer history of New Mexico - Biro Walters, Jordan (Seattle : University of Washington Press, 2023)
"In Wide-Open Desert, Jordan Biro Walters explores the experiences of Pueblo, Navajo, Nuevomexicanx, and white LGBTQ people in New Mexico-many of whom were artists and writers-to examine how their ideas and beliefs about self-expression, political engagement, and race relations transformed American notions of political identity over the course of the twentieth century"--
Introduction: Land of enchantment -- "Going Santa Fe" : the making and unmaking of queer cultures -- Decency debate : the Smoot-Hawley Tariff Act, 1930 -- Land of entrapment : the formation and consequences of the security state, 1945-1960s -- "What to do about homosexuals?" : open secrets and sodomy law, 1953-1963 -- Land of entwinement : rural and urban queer lives -- Offending moral decency : the 1969 "Love-Lust" controversy and gay liberation -- Conclusion: "We never go away."
Description based on print version record.
Includes bibliographical references and index.
JSTOR
Keywords: Sexual minorities -- New Mexico -- History -- 20th century; Sexual minorities -- Identity; New Mexico -- History -- 20th century; Gay liberation movement -- New Mexico -- History -- 20th century; Minorités sexuelles -- Nouveau-Mexique -- Histoire -- 20e siècle.; Minorités sexuelles -- Identité.; Nouveau-Mexique -- Histoire -- 20e siècle.; Mouvement de libération des personnes homosexuelles -- Nouveau-Mexique -- Histoire -- 20e siècle.; HISTORY / United States / State & Local / Southwest (AZ, NM, OK, TX); Gay liberation movement; Sexual minorities; Sexual minorities -- Identity; Queer history; New Mexico; 1900-1999; History